Human(ized) monoclonal antibodies in atopic patients: state of the art - Yalcin, Arzu Didem; Onbasi, Kevser; Uzun, Rusen; Herth, Felix; Schnabel, Philipp Albert (Central European journal of immunology, 2020)
Asthma is an important chronic disease affecting a lot of people worldwide. Treatment options for asthma like biological agents are being developed more frequently nowadays. Despite a lot of treatment options, some patients still remain symptomatic. As more and more practitioners choose treatment...
Gesehen am 17.09.2020